The Negro's Image in the South : The Anatomy of White Supremacy - Nolen, Claude H. (Book collections on Project MUSE., 1968)
Symbolic of the historic conflict between North and South has been the South's attitude toward African Americans. This historical study presents a thorough analysis -- derived from books, periodicals, speeches, sermons, lectures, and other documents -- of the doctrine of white supremacy.